Cobalt-free Ba0.5Sr0.5Fe0.8Cu0.1Ti0.1O3−δ as a bi-functional electrode material for solid oxide fuel cells - Yang, G.; Shen, J.; Chen, Y.; Tadé, M.; Shao, Zongping (Elsevier, 2015)
In this study, we investigate a cobalt-free titanium-doped perovskite oxide with the nominal composition of Ba0.5Sr0.5Fe0.8Cu0.1Ti0.1O3−δ (BSFCuTi) as a potential electrode material for intermediate temperature solid oxide fuel cells (IT-SOFCs). In comparison to Ba0.5Sr0.5Fe0.9Cu0.1O3−δ, BSFCuTi exhibits improved phase stability and a reduced thermal expansion coefficient even though the electrical conductivity decreases. A low area specific resistance of 0.088 Ω cm2 is achieved at 600 °C based on a symmetrical cell test, which is comparable to the result for the benchmark Ba0.5Sr0.5Co0.8Fe0.2O3−δ cobalt-based perovskite electrocatalyst. Stable operation for a period of 200 h is also demonstrated. The I–V test shows a very high power output of 1.16 W cm−2 for a single cell using a BSFCuTi cathode at 600 °C. In addition, the BSFCuTi can be partially reduced under a reducing atmosphere to prepare a suitable anode material. A cell with BSFCuTi as the material for both electrodes and a thick Gd0.2Ce0.8O1.9 electrolyte (300 μm) delivers an attractive power density of 480 mW cm−2 at 800 °C. The high activity, favorable stability and bi-functionality make BSFCuTi a promising electrode material for IT-SOFCs.